Treatment Strategies for the Optimal Management of Locally Advanced Pancreatic Adenocarcinoma With Curative Intent: A Systematic Review. Issue 10 (November 2020) - Attard, Joseph A.; Farrugia, Alexia; Pathanki, Adithya; Roberts, Keith J.; Dasari, Bobby; Isaac, John; Ma, Yuk Ting; Chatzizacharias, Nikolaos A.
Abstract : Abstract: Historically, locally advanced pancreatic adenocarcinoma (LAPDAC) was considered a palliative condition. Advances in treatment have resulted in studies reporting survival after neoadjuvant treatment and surgery similar to earlier disease stages. However, there is no consensus on optimal LAPDAC management. Our aim was a systematic review of published evidence on LAPDAC treatment strategies with curative intent. Twenty-eight studies defining LAPDAC as per established criteria and reporting outcomes after neoadjuvant treatment with a view to resection were included. Primary outcomes were resection rate and proportion of curative resections. Secondary outcomes were postoperative mortality, progression-free survival, and overall survival. Neoadjuvant treatment varied significantly, most common being the combination of folinic acid, fluorouracil, irontecan, and oxaliplatin. Median percentage of patients proceeding to surgery after completion of neoadjuvant pathway was 33.5%. Median resection rate was 25%. Median R0 resection was 80% of resected patients. These outcomes ranged 0% to 100% across studies. Ninety-day postoperative mortality ranged from 0% to 5%. Median progression-free and overall survival for resected patients were 12.9 and 30 months, respectively, versus 13.2 months overall survival for unresected patients. In conclusion, although there is wide variability in reported LAPDAC resection rates post–neoadjuvant chemotherapy, retrospective data suggest that neoadjuvant treatment followed by surgery results in improved survival. Abstract : Supplemental digital content is available in the text.